2007
DOI: 10.1002/ejsp.452
|View full text |Cite
|
Sign up to set email alerts
|

When positive and negative expectancies disrupt performance: regulatory focus as a catalyst

Abstract: The present research investigates the impact of negative and positive stereotypic expectancies on cognitive test performance. A theoretical framework that relates expectancy effects to self-regulatory processes as postulated by Regulatory Focus Theory (RFT) is presented. Building on the differential sensitivity hypothesis proposed in this theoretical model, we argue that when self-regulation in a prevention focus is activated individuals are particularly sensitive with regard to negative cues and therefore neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 48 publications
5
57
0
Order By: Relevance
“…In general, the eagerness of people in a promotion focus results in an increased sensitivity to positive information, whereas the vigilance of individuals in a prevention focus leads to an increased attention to negative information (Keller & Bless, 2008;Pattershall, Eidelman, & Beike, 2012;Wang & Lee, 2006;Yoon, Sarial-Abi, & Gurhan-Canli, 2012). Based on these findings, we demonstrated that the impact of regulatory focus on the selective processing of positive and negative information has an impact on how advertisings that contain positive and negative product-related information are perceived (Florack et al, 2009).…”
Section: Selective Processing Of Informationmentioning
confidence: 66%
See 1 more Smart Citation
“…In general, the eagerness of people in a promotion focus results in an increased sensitivity to positive information, whereas the vigilance of individuals in a prevention focus leads to an increased attention to negative information (Keller & Bless, 2008;Pattershall, Eidelman, & Beike, 2012;Wang & Lee, 2006;Yoon, Sarial-Abi, & Gurhan-Canli, 2012). Based on these findings, we demonstrated that the impact of regulatory focus on the selective processing of positive and negative information has an impact on how advertisings that contain positive and negative product-related information are perceived (Florack et al, 2009).…”
Section: Selective Processing Of Informationmentioning
confidence: 66%
“…The gap between women and men, for example, is substantially larger in math tests that involve point deductions for mistakes than in alternative math tests. Parallel findings documenting particularly strong detrimental effects of negative performance expectancies in prevention-focused test takers were documented in a series of (experimental) studies (Gaillard, Desmette, & Keller, 2011;Keller, 2007;Keller & Bless, 2008). Hence, if the goal were to avoid effects of stereotype threat on the performance of test takers confronted with negative stereotypes, it would be wise to use test methods that activate a promotion focus like tests that allow getting additional points for being successful on additional tasks, and to avoid methods that elicit a prevention focus.…”
Section: Designing Contexts: the Example Of Regulatory Focus And Perfmentioning
confidence: 91%
“…For example, being a target of a negative stereotype cues a motivation to detect, correct and prevent errors as a means to disconfirm that stereotype (Forbes, Schmader, & Allen, 2008;Jamieson & Harkins, 2007;Keller & Bless, 2008). Ironically, the very feedback that minority students might most be searching for and motivated to learn from could be systematically withheld from them.…”
Section: Introductionmentioning
confidence: 94%
“…Challenge appraisal, conversely, facilitates performance by inducing adaptive stress responses and preparing the perceiver to address the stress (Scheepers, 2009;Vick, Seery, Blascovich, & Weisbuch, 2008). Importantly, people might interpret the same task as a challenge or a threat, depending on a range of situational factors, like the negative consequences of failure (e.g., Keller & Bless, 2008). Given the divergent consequences of threat and challenge appraisals for performance, reframing an otherwise threatening task as a challenge might reduce the effects of stereotype threat.…”
Section: Introductionmentioning
confidence: 94%